Respuesta :

Answer:

Step-by-step explanation:

Given that:

[tex]x^2 + z^2 \leq 36[/tex]

if we assume that x is zero, then [tex]z^2 = 36[/tex] , [tex]z = \pm \sqrt{36}[/tex] [tex]z = \pm 6[/tex] i.e the radius of the circle goes from -6 to +6, Similarly, if we assume that z is zero, then [tex]x^2 = \pm 36[/tex] , [tex]x = \pm \sqrt{36}[/tex] , [tex]x = \pm 6[/tex] . This implies that [tex]x^2 + z^2[/tex] describes the circle with radius 6

[tex]x^2 + z^2 \leq 36[/tex] is an equation at region which consist of those points whose distance  from the centre is at least with radius -6 and at most 6.

Therefore, the region is the solid cylinder of radius 6, where the Y axis is also the axis of the cylinder.